Anatomy of Social Conflict and Efforts at Integration Reconstruction in Multicultural Indonesian Society After the Reform Era (International Journal of Economics Management and Social Science, 2026)
Background: The collapse of the New Order regime in 1998 unleashed a wave of social conflicts across Indonesia—ethnic, religious, separatist, and resource-based—that tested the structural integrity of one of the world's most diverse nations. More than two decades after Reformasi, the anatomy of these conflicts and the effectiveness of integration reconstruction efforts remain critically important subjects for sociological inquiry. Objective: This study analyzes the structural anatomy of social conflicts in post-Reform Indonesia and evaluates efforts at social integration reconstruction in the context of multicultural society. Methods: A systematic literature review was conducted using Scopus, Web of Science, and Google Scholar, covering publications from 2019 to 2025 on Indonesian social conflict, multiculturalism, post-conflict reconstruction, and social integration. Results: Findings reveal that post-Reform social conflicts are rooted in overlapping structural factors including democratic transition instability, decentralization tensions, economic inequality, identity politicization, and unresolved historical grievances. Integration reconstruction has achieved partial success through peace agreements, interfaith dialogue, and autonomy frameworks, but remains incomplete due to elite capture, inequality persistence, and weak civic institutions. Conclusion: Sustainable social integration in multicultural Indonesia requires structural approaches that address root causes of conflict, strengthen civil society, and build institutional trust, rather than relying exclusively on ceremonial multiculturalism or elite pact-making.